Türkiye Yüzyılı Maarif Modeli Hayat Bilgisi Dersi Öğretim Programındaki Öğrenme Çıktılarının, Yenilenmiş Bloom Taksonomisi ve Sürdürülebilir Kalkınma Hedeflerine göre Değerlendirilmesi. - UĞRAŞ, Hilal (Electronic Turkish Studies)
The purpose of this study is to evaluate the learning outcomes included in the Life Skills Course Curriculum prepared within the scope of the Türkiye Century Education Model in terms of the Revised Bloom Taxonomy (RBT) and the Sustainable Development Goals (SDGs). In this study, document analysis, a qualitative research method, was used to examine the total of 66 learning outcomes (1st grade: 23, 2nd grade: 23, 3rd grade: 20) in the Life Studies Course Curriculum published in 2024. The analysis revealed that most of the learning outcomes in the 1st grade were at the “understanding” level, in the 2nd grade at the ‘application’ level, and in the 3rd grade at higher cognitive processes such as “application, analysis, and evaluation.” All learning outcomes across all grade levels were directly related to SDG 4: Quality Education; and that they also have multifaceted connections with SDGs 3: Good Health and Well-Being, SDG 11: Sustainable Cities and Communities, SDG 13: Climate Action, SDG 15: Life on Land, and SDG 16: Peace, Justice, and Strong Institutions. The findings show that the Life Studies Course Curriculum aims to instill fundamental values such as cognitive development, sustainable development, environmental responsibility, and social awareness at an early age. These results indicate that teaching programs structured at the primary school level must be developed in a manner consistent with both pedagogical and global sustainability goals. In future research, it may be recommended to analyze different curricula (e.g., Science, Social Sciences, or Turkish) within the framework of RBT and SDG in order to enable interprogram consistency and comparative evaluation.